Integrative taxonomy of the Asian skinks Sphenomorphus stellatus (Boulenger, 1900) and S. praesignis (Boulenger, 1900) with the resurrection of S. annamiticus (Boettger, 1901) and the description of a new species from Cambodia - Grismer, L. Lee; Wood, Perry L., Jr.; Quah, Evan S. H.; Anuar, Shahrul; Poyarkov, Nikolay A.; Thy, Neang; Orlov, Nikolai L.; Thammachoti, Panupong; Seiha, Hun (Zootaxa, 2019)
Molecular phylogenetic analyses of the sister species Sphenomorphus stellatus and S. praesignis based on the mitochondrial genes 12S and 16S rRNA recover the former as paraphyletic with respect to the latter in that a specimen of S. stellatus from the type locality in Peninsular Malaysia is more closely related to S. praesignis than to Indochinese populations of S. stellatus. Furthermore, the phylogeny indicates that the Indochinese populations represent two species, thus resulting in four major lineages within this clade. These relationships are consistent with multivariate and univariate analyses of morphological and discrete color pattern data which statistically define and diagnose the four lineages and together with the molecular data, provide the foundation for robust, testable, species-level hypotheses. As such, S. stellatus is herein restricted to Peninsular Malaysia; S. annamiticus is resurrected for the circum-continental populations ranging through southeastern Thailand, southern Cambodia, and southern Vietnam; a new species—S. preylangensis sp. nov.—is described from an isolated mountain, Phnom Chi, from the Prey Lang Wildlife Sanctuary in central Cambodia; and the taxonomy of S. praesignis remains unchanged. The description of S. preylangensis sp. nov. underscores the necessity to conserve this remnant of lowland evergreen rainforest in the Prey Lang Wildlife Sanctuary.